FGF21-dependent alleviation of cholestasis-induced liver fibrosis by sodium butyrate - Yang, Jing; Chen, Lei; Zhao, Shan-Shan; Du, Chuang; Fan, Yi-Zhe; Liu, Hui-Xin; Li, Yongchun; Li, Yong-Zhi (Frontiers in Pharmacology, 2024)
Background The beneficial effects of fibroblast growth factor 21 (FGF21) and sodium butyrate (NaB) on protection against cholestasis-induced liver fibrosis are not well known. This study aimed to explore the effects of FGF21 and NaB on bile duct ligation (BDL)-induced liver fibrosis. Methods Wild-type (WT) and FGF21 knockout (KO) mice received BDL surgery for 14 days. Liver fibrosis was assessed by Masson’s staining for fibrosis marker expressions at the mRNA or protein levels. Adenovirus-mediated FGF21 overexpression in the WT mice was assessed against BDL damage. BDL surgeries were performed in WT and FGF21 KO mice that were administered either phosphate-buffered saline or NaB. The effects of NaB on the energy metabolism and gut microbiota were assessed using stable metabolism detection and 16S rRNA gene sequencing. Results BDL-induced liver fibrosis in the WT mice was accompanied by high induction of FGF21. Compared to the WT mice, the FGF21 KO mice showed more severe liver fibrosis induced by BDL. FGF21 overexpression protected against BDL-induced liver fibrosis, as proved by the decreasing α-SMA at both the mRNA and protein levels. NaB administration enhanced the glucose and energy metabolisms as well as remodeled the gut microbiota. NaB alleviated BDL-induced liver fibrosis in the WT mice but aggravated the same in FGF21 KO mice. Conclusion FGF21 plays a key role in alleviating cholestasis-induced liver damage and fibrosis. NaB has beneficial effects on cholestasis in an FGF21-dependent manner. NaB administration can thus be a novel nutritional therapy for treating cholestasis via boosting FGF21 signaling and regulating the gut microbiota.